Effect of grain size and crystal orientation on the corrosion behavior of as-extruded Mg-6Gd-2Y-0.2Zr alloy. (March 2020) - Luo, Yaofeng; Deng, Yunlai; Guan, Liqun; Ye, Lingying; Guo, Xiaobin; Luo, An
Graphical abstract: Highlights: The direct observation of corrosion process is performed by EBSD. The small grains corrode easily. There is almost no corrosion attack suffered by the largest grain with (10-10) non-basal orientation. Under the similar grain size condition, the non-basal plane is more vulnerable to corrosion than the basal plane. Abstract: The influence of grain size and crystal orientation on the corrosion behavior of as-extruded Mg-6Gd-2Y-0.2Zr alloy is investigated by scanning electron microscopy (SEM), electron backscatter diffraction (EBSD). The EBSD system is used to characterize the grain size, crystal orientation and corroded surface. By investigating the corrosion process of as-extruded Mg-6Gd-2Y-0.2 Zr alloy, we can observe that the smaller grains and (10-10)/(11-20) non-basal planes are more susceptible to corrosion in the aggressive corrosion environment. Furthermore, the relationship between the corrosion rate and grain size is connected with the crystal orientation and whether the passivation occurs.